Diversity and Inclusion Initiatives in Brazilian Software Development Companies: Comparing the Perspectives of Managers and Developers - Poncell, Igor; Gama, Kiev (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2022)
The search for diversity and inclusion (D&I) in Software Development companies around the world is becoming more common. This change is due both to the understanding of the need to include underrepresented groups, but also to the use of diversity as a business tool to improve the image and even increase performance and profit. The process of adapting the work environment to a diverse and inclusive context requires an effort beyond prospecting people from underrepresented groups. Such effort can range from an analysis of who makes up the company and which groups need attention, training of leaders and even structural changes in the physical work environment. This paper seeks to bring an analysis of the perception of D&I in companies, both on the part of developers and management, collecting opinions, practices and problems through qualitative research. As a result of the present study, we see that companies have an interest in improving the work environment and have put an effort to achieve it. However, when we contrast the management perspective with the point of view that developers have, we realize that some points go unnoticed and do not receive attention. It causes underrepresented groups to end up not having their concerns discussed within the companies. Through this study, it is possible to understand some obstacles and failures that some companies are committing in their attempt to improve D&I.